THE IMPORTANCE OF SPORTS MEDICINE IN THE TREATMENT OF SPORTS INJURIES FOR FOOTBALL PLAYER’S FIR CLASSIN ANBAR PROVINCE - Al-Modhini, Alaa El-Din Abdullah Taha (International Journal of Psychosocial Rehabilitation, 2020)
The aim of this research is to demonstrate the importance of sports medicine in the treatment of sports injuries for first class football players in the Iraqi Anbar province. The descriptive method is used to suit the nature of the research problem. The research community of all first-class football players in Anbar province was identified. The research sample was deliberately tested with an estimated 60 players.